2006
DOI: 10.1590/s0100-879x2006000800005
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary esophageal contractions in patients with gastroesophageal reflux disease

Abstract: We studied the primary and secondary esophageal peristalsis in 36 patients with heartburn and acid regurgitation and in 14 asymptomatic volunteers. Primary peristalsis was elicited by ten swallows of a 5-mL bolus of water and secondary peristalsis was elicited by intra-esophageal infusion of 5, 10, and 15 mL water, 0.1 N hydrochloric acid and air. Esophageal contractions were measured by an 8-lumen manometric catheter assembly incorporating a 6-cm sleeve device. Contractions were registered at 3, 9, and 15 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
1
3
0
1
Order By: Relevance
“…ineffective (61.8%-88.6%), low pressure amplitude in both the distal and proximal esophagus results in 38.5% IEM of primary peristalsis, and more synchronous contractions in secondary peristalsis result in IEM in patients with GERD-CC. Those findings are consistent with impairment of primary and secondary peristalsis leading to ineffective esophageal clearance and prolonged exposure to acid 43,44. Thus, we might extrapolate that low pan-esophageal pressure amplitude in primary peristalsis and synchronous contraction in secondary peri-No coughing was recorded in 16.1% of patients with GERD-CC.…”
supporting
confidence: 80%
“…ineffective (61.8%-88.6%), low pressure amplitude in both the distal and proximal esophagus results in 38.5% IEM of primary peristalsis, and more synchronous contractions in secondary peristalsis result in IEM in patients with GERD-CC. Those findings are consistent with impairment of primary and secondary peristalsis leading to ineffective esophageal clearance and prolonged exposure to acid 43,44. Thus, we might extrapolate that low pan-esophageal pressure amplitude in primary peristalsis and synchronous contraction in secondary peri-No coughing was recorded in 16.1% of patients with GERD-CC.…”
supporting
confidence: 80%
“…It is possible, however, that patients with severe IOM had impaired secondary peristalsis. 40 Our study showed an important overlap in values of acid exposure between patients with mild-andsevere IOM. Furthermore, the presence of hiatal hernia and male sex may significantly impact acid exposure in patients with mild IOM.…”
Section: Discussionmentioning
confidence: 49%
“…There are experimental studies that report reversibility of esophageal hypomotility after healing of inflammation. 36, 37, 38 Fornari and colleagues reported a transient reversibility of over 50% in 11 patients with severe IEM after adequate cholinergic stimulation of the esophagus. 34 However, other studies show that patients with chronic erosive GERD did not recover from esophageal dysmotility after pharmacological or surgical treatment of their reflux disease.…”
Section: Discussionmentioning
confidence: 99%